Concepting virtual tour using panoramic photography as tourism promotional media for the Maimun area, Indonesia - Wardani, Winny Gunarti Widya; Syahid, Syahid; Destiadi, Rezha; Winarni, Rina Wahyu (Humanities, Arts and Social Sciences Studies, 2026)
Indonesia has many cultural heritage sites, such as the Maimun area in Medan, North Sumatra, with the potential to become tourist destinations. This area is a historical site designated as a cultural heritage and has attracted the attention of investigators due to the urgency of developing a Virtual Reality (VR)-based tourism promotion medium. The option to develop a virtual tour as a technology-based tourism promotion allows information to be packaged in a more informative and interactive manner. Therefore, this research aimed to describe the principles of panoramic photography in conceptualizing a virtual tour to build user understanding while enjoying 360-degree panoramic visualization. Quantitatively, questionnaires were distributed to young people as respondents to determine the views on the cultural value potential of the Maimun area. Qualitatively, the analysis of the virtual tour concept applied landscape photography genres and compositional theory to establish depth and direct viewer attention through perspective. The results showed that the conceptualization of a 360-degree virtual tour using panoramic photography adopted a variety of high-angle and eye-level shooting methods. This was carried out because the concept was necessary to show details of the exterior and interior of buildings, ornaments, park areas, monuments, and public spaces. Meanwhile, variations applied one-point, two-point, and three-point perspectives in a balanced manner. This research was expected to serve as an academic reference for designing tourism promotion media within the concept of a 360-degree panoramic virtual tour to transmit cultural messages, while supporting the development of creative economic products.